Literary work by Gerold Tietz – Literary Engagement of an expelled German - Kubica, Jan (Acta Universitatis Lodziensis. Folia Germanica, 2020)
Gerold Tietz was born in 1941 in Horka (north Bohemia) in a family of Sudeten Germans. Germans lived in this village together with Czechs, Roma people and Jews. The family also involved Czech relatives and many of German relatives spoke good Czech and kept relations with Czech cultural groups. After the war Gerold Tietz and his family were expelled to Swabia. He studied history, French and political science. From 1969 the graduated historian lived in Esslingen where he taught in the grammar school for thirty years. In the autobiographically oriented novels Böhmische Fuge (1997), Böhmisches Richtfest (2007) and in Böhmische Grätschen (2009) Tietz tried to depict official social-political events connected with famous political and cultural figures as well as the stories of ordinary days of “small people” who had to face the consequences of historic changes which influenced their lives. The paper analyses the conditions of Czech and German coexistence and confronts the authentic historic context. Nevertheless, negative features of these ethnic groups are not overlooked and the positive ones are presented as a positive contribution to the current European multiculturalism.